A Qualitative Study Examining the High Turnover Rate of High School Principals in Southwest Georgia and Northwest Florida - Brand, Elizabeth (My University, 2025)
The purpose of this study was to examine the challenges and barriers to reducing the turnover rate of high school principals in Southwest Georgia and Northwest Florida as perceived by identified successful high school principals who have left this position. The high school principal turnover rate is high and increasing, resulting in a loss of resources expended on principal recruitment, selection, development, and retention while also adversely affecting student achievement (Bartanen et al., 2019). A qualitative approach was applied in this study to analyze data collected from identified high school principals and two teachers per principal participant who worked with the identified principal participant. An Interpretive Phenomenological Analysis was used to explore each participant’s lived experience and to identify themes.
Keywords: Dissertations, Academic--United States; Educational leadership; Electronic records; Florida; High school principals; Labor turnover; Public schools; School administrators; Teacher-principal relationships; Valdosta State University; Georgia